Biocompatible melanin based theranostic agent for in vivo detection and ablation of orthotopic micro-hepatocellular carcinoma. (30th June 2020) - Chen, Kang; Li, Qiaolin; Zhao, Xingyang; Zhang, Jinde; Ma, Haosong; Sun, Xiang; Yu, Qian; Zhang, Yueming; Fang, Chihua; Nie, Liming
Abstract : Enhanced photoacoustic performance and therapeutic outcomes of melanin-based organic agents for dual-modality imaging and photothermal ablation of orthotopic hepatocellular carcinoma. Abstract : Early diagnosis and therapy of hepatocellular carcinoma (HCC) is critical to improve the five-year survival rates of patients. Theranostic agents synergized with photothermal ablation are expected to realize the early detection and treatment of orthotopic HCC. However, conventional metallic nanoagents are limited by their potential bio-toxicity to surrounding normal organs. Recently, endogenous biological melanin pigments have been utilized to develop nanoplatforms due to their excellent biocompatibility and degradability. Whereas, the insufficient capability of PEGylated melanin nanoparticles (PEG-MNPs) in photoacoustic (PA) imaging limits their further biomedical applications. Paradoxically, it is difficult to meet these two different requirements. Herein, a multifunctional nanoagent based on melanin (MNPs) conjugating the near-infrared (NIR) dye IR820 was successfully designed and fabricated. Encapsulation by polyethylene glycol (PEG) renders the solubility in water and allows the physical absorption of IR820 for enhanced photoacoustic (PA) performance and photothermal therapy. Besides, PEG coating on the surface of IR820-PEG-MNPs resulted in a reduction in swallowing in the reticuloendothelial system of the liver and spleen, prolonging the circulation time in the blood and increasing the accumulation in the tumor. The IR820-PEG-MNPs displayed satisfactory PA and T 1 -weighted magnetic resonance imaging (MRI) signals in aqueous solution as well as strong photothermal efficiency. Compared with prior injection, PA/MR signals of the tumor region were enhanced by 4.13- and 1.60-fold, respectively, which could effectively detect lesions smaller than ∼1.8 mm. Furthermore, the high photothermal conversion efficiency (40.2%) endowed the IR820-PEG-MNPs with the capability of selectively ablating tumors in orthotopic HCC mouse models under the guidance of PA/MR imaging. This work broadens the biomedical applications of melanin-based agent, which are promising for the precise diagnosis of orthotopic micro HCC and imaging guided photothermal ablation.